Optimization of Pengga Reservoir in The Mandalika Special Economic Zone for Irrigation and Water Supply - Agastya, Dewandha Mas; I Wayan Yasa; I Dewa Gede Jaya Negara (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2024)
Mandalika Special Economic Zone is tourism area that is expected to improve the economy in West Nusa Tenggara Province. To support these activities, an allocation of domestic water needs of 200 liters second -1 is needed. The potential availability of water in the Pengga Reservoir is planned to be a source of domestic water needs in the Mandalika Special Economic Zone. Pengga Reservoir has an effective storage volume of 17.26 MCM. Potential water resources in Pengga Reservoir are obtained from reservoir outflow upstream and lateral inflow from several tributaries. The study was carried out to determine the reservoir storage capacity to meet domestic water needs and irrigation water needs covering an area 3189 ha. The cropping pattern used in the Pengga irrigation area is Paddy – Paddy/Secondary Crops – Paddy/Secondary Crops. To optimize the potential of water resources in the Pengga Reservoir, a linear programming optimization method is used. Indicators of the success of optimization calculations are indicated by the value of cropping intensity, k factor and reliability that have met the minimum limit value. The k factor value for irrigation water needs is 0.70 and domestic water needs is 0.85. Based on the optimization results, it is known the largest annual cropping intensity value occurs in the November I planting season. This conclusion can be seen from the comparison of annual cropping intensity values for the November I and November II planting schedules for the dry year inflow discharge scenario of 99.98% and 97.22% respectively. The cropping intensity value in the November I planting season is greater than November II, namely 100% and 97.25%, for the normal year discharge inflow scenario. This study provides an information for policy makers can use the November I planting schedule to obtain values for maximum cropping intensity and domestic water requirements.